An Aqueous Sodium Ion Hybrid Battery Incorporating an Organic Compound and a Prussian Blue Derivative. Issue 12 (19th April 2014) - Kim, Dong Jun; Jung, Young Hwa; Bharathi, K. Kamala; Je, Sang Hyun; Kim, Do Kyung; Coskun, Ali; Choi, Jang Wook
<x xml:space="preserve">Abstract</x> An aqueous sodium ion hybrid battery consisting of disodium naphthalenediimide salt (anode) and KCo0.5Cu0.5Fe(CN)6 (cathode) is reported. Both electrode materials are inexpensive and exhibit appropriate operating voltages and robust reversibility under neutral aqueous electrolyte conditions, delivering a full‐cell voltage of 1.1 V with 88% capacity retention after 100 cycles. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>